The development design model in the competitiveness of intelligent business organisations - Stipanović, Christian (Array, 2008)
Abstract: Croatian hotel and tourism companies are failing to keep abreast of modern tourism trends in the globalised marketplace of the twenty-first century. The imperative is to innovate the development design model based on a new value system. A precondition to success is transforming sluggish, inert companies that live according to the mindset of the past century into high-growth intelligent organisations capable of actively creating the future.The intelligent business organisation, founded on a new generation of managers, employee empowerment, software solutions and expert systems, needs to manage data and information to generate new development trends. The aim is to valorise intellectual capital and information in making innovations and creating new solutions in order to be able to stand up to rivals and more fully meet the needs of clients